The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/1519-6984.18513
|View full text |Cite
|
Sign up to set email alerts
|

Two common species dominate the species-rich Euglossine bee fauna of an Atlantic Rainforest remnant in Pernambuco, Brazil

Abstract: Nowadays, the northern part of the Atlantic Rainforest of Brazil is largely destroyed and forest remnants rarely exceed 100 ha. In a 118 ha forest fragment within a state nature reserve of Pernambuco (Reserva Ecológica Gurjaú), we surveyed the orchid bee fauna (Apidae, Euglossini) using eight different scent baits to attract males. Once a month during one year, the bees were actively collected with entomological nets, from November 2002 to October 2003 by two collectors. We collected 2,908 orchid bee males bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The most abundant species in both years was Euglossa cordata with 384 males (corresponding to 78.5% and 83.2% in 2015 and 2016, respectively), followed by Eulaema nigrita with 86 males (19.3% and 14.7% in 2015 and 2016, respectively) ( Table 1). Euglossa cordata and Eulaema nigrita were also the two-dominant species in the Santa Genebra forest in 2008 (Cordeiro et al, 2013) and in other Atlantic Forest fragments Gaglianone, 2008, 2012;Ramalho et al, 2009;Rocha-Filho and Garófalo, 2013;Oliveira et al, 2015). Both species are distributed throughout the Atlantic Forest (Garraffoni et al, 2017), and can be found in disturbed and fragmented areas as well as in open preserved areas (e.g., Viana and Kleinert, 2006;Ramalho et al, 2009;Aguiar and Gaglianone, 2012).…”
mentioning
confidence: 97%
“…The most abundant species in both years was Euglossa cordata with 384 males (corresponding to 78.5% and 83.2% in 2015 and 2016, respectively), followed by Eulaema nigrita with 86 males (19.3% and 14.7% in 2015 and 2016, respectively) ( Table 1). Euglossa cordata and Eulaema nigrita were also the two-dominant species in the Santa Genebra forest in 2008 (Cordeiro et al, 2013) and in other Atlantic Forest fragments Gaglianone, 2008, 2012;Ramalho et al, 2009;Rocha-Filho and Garófalo, 2013;Oliveira et al, 2015). Both species are distributed throughout the Atlantic Forest (Garraffoni et al, 2017), and can be found in disturbed and fragmented areas as well as in open preserved areas (e.g., Viana and Kleinert, 2006;Ramalho et al, 2009;Aguiar and Gaglianone, 2012).…”
mentioning
confidence: 97%
“…violacea on Site A. Euglossa cordata was the most common species on site D1-2 and was also quite abundant on site B, but not on site A (only one specimen collected). These results show that there is no clear pattern of dominance on the local assemblages, unlike what occurs in different areas of Atlantic forest where a single or a few common species dominate the local faunas (e.g., Aguiar & Gaglianone, 2012;Oliveira et al, 2015). Besides the alleged existence of heterogeneity among samples of euglossine bees taken from nearby sites (Armbruster, 1993), this study was carried out towards the range limits of most species, where the populations are regarded to be highly fragmented (reviewed in Gaston, 2009).…”
Section: Local Faunasmentioning
confidence: 95%
“…Moreover, most studies on "urban bees" in the tropics seem not to be carried out in heavily modified urban habitats, but on natural vegetation remnants or orchards surrounded by the urban matrix (e.g., Antonini et al 2013;Cândido et al 2018;Tangtorwongsakul et al 2018;Wayo et al 2020), in contrast to how studies are often conducted in temperate areas. Furthermore, many studies are faunal surveys of urban green areas (e.g., Nemésio and Silveira 2007;Gazola and Garófalo 2009;Nemésio and Silveira 2010;Aidar et al 2013;Viotti et al 2013;Oliveira et al 2015;Possamai et al 2017), not specifically assessing the effect of urbanization-related variables on bee communities. Therefore, more research specifically evaluating local and landscape characteristics needs to be conducted in tropical cities to understand the impacts of urbanization and to enhance the conservation value of cities for bees and other pollinators (Hernandez et al 2009).…”
Section: Insects (Bees)mentioning
confidence: 99%